Two new species of the armored spider genus Tetrablemma O. P.-Cambridge, 1873 from northern South America (Araneae: Synspermiata: Tetrablemmidae) - Martínez, Leonel; Flórez D, Eduardo; Brescovit, Antonio Domingos (Zootaxa, 2020)
Two new species of the armored spider genus Tetrablemma O. P.-Cambridge, 1873 from Colombia and Venezuela are herein described and illustrated: Tetrablemma tatacoa sp. nov. from Huila department, Colombia and T. mochima sp. nov. from Sucre state, Venezuela. These species represent the second record of the genus in the New World. Specimens of these new species were collected in pristine ecosystems, which suggests a natural Gondwanan distribution of the genus. Additionally, a distribution map of the Tetrablemma species in America is herein included.